Early Marriage in Indonesia Islamic Family Law Perspective - Mahendra, Mahendra; Maisuri, Violis (MILRev: Metro Islamic Law Review, 2022)
Child marriage is a social phenomenon that is common in all places. This kind of marriage is like an iceberg phenomenon that appears a little on the surface, is rarely disclosed, but is commonly practiced in the wider community. Child marriage has become one of the most controversial issues in Islamic family law. Some scholars approve of the practice without disapproval while others do not. The substance of Islamic law is to create a better life for society today and in the future. If it is found that child marriage in contemporary society has caused many negative impacts, then this matter must be legally rejected.